2021
DOI: 10.3390/cancers13225666
|View full text |Cite
|
Sign up to set email alerts
|

The Classification of Myeloproliferative Neoplasms: Rationale, Historical Background and Future Perspectives with Focus on Unclassifiable Cases

Abstract: Myeloproliferative neoplasms (MPNs) are a heterogeneous group of clonal hematopoietic stem cell disorders, characterized by increased proliferation of one or more myeloid lineages in the bone marrow. The classification and diagnostic criteria of MPNs have undergone relevant changes over the years, reflecting the increased awareness on these conditions and a better understanding of their biological and clinical-pathological features. The current World Health Organization (WHO) Classification acknowledges four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…However, in most instances, clinical and laboratory findings coupled with the molecular search for driver mutations and/or molecular or cytogenetic markers of clonality of hematopoiesis and BM biopsy examination prompt the diagnosis. 19 From the histopathologic perspective, mimickers of MPN include immune thrombocytopenia (ITP) treated with agonists of thrombopoietin receptor that impart a striking MPN-like histologic appearance to BM biopsy, and the rare instances of autoimmune myelofibrosis, a condition in which the coexistence of lymphoid infiltrate may further trigger a diagnosis of lymphoproliferative disorder. 20,21 Spleen histology is less frequently experienced in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most instances, clinical and laboratory findings coupled with the molecular search for driver mutations and/or molecular or cytogenetic markers of clonality of hematopoiesis and BM biopsy examination prompt the diagnosis. 19 From the histopathologic perspective, mimickers of MPN include immune thrombocytopenia (ITP) treated with agonists of thrombopoietin receptor that impart a striking MPN-like histologic appearance to BM biopsy, and the rare instances of autoimmune myelofibrosis, a condition in which the coexistence of lymphoid infiltrate may further trigger a diagnosis of lymphoproliferative disorder. 20,21 Spleen histology is less frequently experienced in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic trephine biopsies showed age‐adjusted hypercellularity in the majority of cases (67%), increased (100%) and clustered (83%) MKC and a median (range) WHO fibrosis score of 1 (0–3). As highlighted by Pizzi et al, 6 this suggests that most new MPN‐U, diagnosed according to WHO 2016 criteria, fall within the early, non‐fibrotic and non‐advanced stage. Kim et al 12 characterised 199 MPN patients, eight of whom had MPN‐U, where CALR was the most frequent mutation, although it must be noted that this conclusion is limited by the small numbers of patients.…”
Section: Distinguishing Mpn‐u From Mds/mpn‐u: Focus Pointmentioning
confidence: 92%
“…Perhaps representing an arbitrarily defined early/prodromal phase, 21 cases could be re-classified as ET or PV whereas within the advanced phase, the vast majority could be reclassified as overt MF (25) and PV (6). The authors reported that this was most likely reflective of refined definition of prefibrotic MF and overtly fibrotic MF and updated Hb/haematocrit values within the PV category.…”
Section: Morphological and Molecular Characterisation Of Mpn-u: A Mov...mentioning
confidence: 99%
See 2 more Smart Citations